Birth seasonality studies in a large Prader–Willi syndrome cohort. Issue 8 (21st June 2019) - Butler, Merlin G.; Kimonis, Virginia; Dykens, Elisabeth; Gold, June Anne; Tamura, Roy; Miller, Jennifer L.; Driscoll, Daniel J.
Abstract: Prader‐Willi syndrome (PWS) is generally due to sporadic paternal deletions of the chromosome 15q11‐q13 region followed by maternal disomy 15. Advanced maternal age is more commonly seen in those with maternal disomy 15. Environmental factors (e.g., drug use, occupational chemical exposure, infectious agents, and irradiation) could account for chromosome changes. Previous evidence of differences in male and female gametogenesis could suggest an environmental role in the causation of the paternal 15q11‐q13 deletion seen in PWS. Certain occupations such as hydrocarbon‐exposing occupations (e.g., landscaping, farming, and painting) and viral exposure (e.g., human coronavirus 229E causing upper respiratory infections in adults with an incorporation site in the human genome at chromosome 15q11) can be seasonal in nature and contribute to chromosome damage. To assess, we reviewed birth seasonality data in a large cohort of individuals with PWS recruited nationally ( N = 355) but no significant differences were seen by month between those with the 15q11‐q13 deletion compared with maternal disomy 15 when analyzing quarterly seasonal patterns. Although early evidence supported birth seasonality differences in PWS, a larger number of individuals in our recent study using advanced genetic testing methods did not find this observation.